Patient Safety Culture and Safety Attitudes in the Estonian Context: Simultaneous Bilingual Cultural Adaptation and Validation of Instruments - Asi, Signe; Calsbeek, Hiske; Kangasniemi, Mari Katariina; Vähi, Mare; Põlluste, Kaja (FRONTIERS MEDIA SA, 2025)
Objectives: This study aimed to simultaneously and bilingually validate the Hospital Survey on Patient Safety Culture (HSOPSC 2.0) and the Safety Attitudes Questionnaire (SAQ).
Methods: The validation included translation, cultural adaptation, and assessment of validity and consistency. Data were collected in three hospitals in 2022 via online and paper surveys, with Estonian- and Russian-speaking employees participating.
Results: In total, 579 (30%) participants from the three hospitals completed both questionnaires. Among them, 293 (51%) were Russian-speaking and 286 (49%) were Estonian-speaking. Cronbach's alpha hy for HSOPSC 2.0 was >= 0.60, except in the Russian version for the three dimensions. Cronbach's alpha for SAQ was >= 0.60, except in the Russian version for one dimension. Pearson's correlations of the Estonian HSOPSC 2.0 ranged from 0.26 to 0.60 and in the Russian version from 0.18 to 0.47.
Conclusion: The validity of the HSOPSC 2.0 and SAQ questionnaires was confirmed in the Estonian versions. Minor corrections were recommended for the Russian. Both versions are considered suitable for assessing PSC in Estonian hospitals.